Development of Learning Media LENTERA (Ludo Edukasi Menyenangkan dan Ceria) to Increase the Activeness of Class VIII Students - Samsul Bahri; Neni Wahyuningtyas (STKIP Taman Siswa Bima, 2025)
Interesting and interactive learning media is the key in increasing student learning activeness in social studies subjects, especially in the material about the process of implementing Indonesian Independence. The lack of active participation of students so far has encouraged this research to develop interactive learning media in the form of a game called LENTERA (Ludo Edukasi Menyenangkan dan Ceria). During this time, learning history tends to be monotonous and less directly involves students, so innovation is needed in the form of media that can motivate them to be more active. This research aims to develop a game-based interactive learning media called LENTERA to increase the activeness of grade VIII students. This research uses the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. LENTERA media was developed by integrating a Game-Based Learning approach to create a more fun and meaningful learning atmosphere. The results of validation from experts, this media is declared very feasible to be applied, with the results of material expert validation of 87% and media expert validation of 89%. Implementation in class VIII F SMPN 10 Malang showed an increase in student activeness by 90%. This media also proved to be able to create a fun and collaborative learning atmosphere. Future research is recommended to develop a digital version to increase accessibility and flexibility of learning